MODIFIKASI MESIN TRIM FORM PADA PROSES PENGEMASAN INTEGRATED CIRCUIT UNTUK PENURUNAN DAMAGED LEAD - Nur Sakinah Asaad; Purwanto Purwanto (JURNAL INTEGRASI, 2020)
Integrated circuit (IC) packaging process of Low Profile Quad Flat Package (LQFP) needs trim form machine for trimming the dambar and forming the IC leads before separated from the lead frame. One of the process sequences in trim form machine is offload, placement of IC units in the tray by pick and place module including open and close of turn table movement to adjust space between lead frame columns before transferred to tray. Open and close movement of the turn table impact to damaged lead production defect. Modification intended to misalignment earlier detection so that the machine can stop automatically and decrease production defect by adding two proximity sensor on turn table. Based on the result of this research, the error on turn table could be reduced to 88% with assembly yield achieved 99.985% or increase up to 0.07%.